Role of work stress and organizational commitments in educating workload effect on intention to quit - Christy, Maria Yasinta Palma; Priartini, Putu Saroyini (International research journal of management, IT and social sciences, 2019)
This research aimed at analyzing the mediation role of job stress and organizational commitment in the effect on workload through the employees’ intention to quit. There are 86 respondents in this research which consist of all department operational. The test was done with the PLS method (Partial Least Square) by using smart PLS. Based on the result of analysis it can be concluded that the workload gives a positive contribution to job stress, the workload contributes negatively to the organizational commitment, job stress contribute positively to the intention to quit, the organization commitment contribute negatively to the intention to quit, the workload contribute positively to the intention to quit, job stress mediates partially the relationship between workload employee intention to quit, and organizational commitment mediates partially the relationship between workload employee intention to quit.